La estructura familiar y las conductas agresivas, de los estudiantes de bachillerato común del colegio experimental Bernardo Valdivieso de la ciudad de Loja, año lectivo 2012-2013 - Chamba Correa, Verónica Jeanneth (2015)
This research aims is analyzing the family structure and its relationship with the aggressive behavior of common school students of Bernardo Valdivieso Experimental High School of Loja city. Descriptive type study, transversal cut, Methods used scientific, inductive, deductive, descriptive, analytic-synthetic. The survey was used and aggressiveness questionnaire by Buss and Perry applied in a sample of 188 students. Results: of the survey, 57.45% live with both parents and 65.43% said they have a good relationship; from aggressiveness questionnaire 47.34% state that physical aggression in middle level. It concludes that according to family structure, It was found that most students belong to a type of nuclear family, on the other hand they have physically aggressive behavior at a medium level. Between family structure and aggressive behavior of common school students of Bernardo Valdivieso Experimental High School